Unchaining factors in the entrepreneurial career decision (2010)
This research’s objective is to know and describe the predisposition factors, the unchaining factors and the maintenance factors in the development of the Entrepreneurial Career of a group of entrepreneurial professionals. The research was based in Dyer’s Entrepreneurial Career developed in 1994, the career planning concepts of Schein and contributions from other researchers. The sample used was made of forty-four Business Administration, Systems Engineering and Industrial Engineering graduates from three universities from the city of Cali, Colombia, who actually manage their own company or work for family business. The research used the “In-depth interview technique”, carried out by psychologists, in order to investigate aspects like family environment, educational development, juvenile experiences, managerial development stages and many other psycho-social aspects related to the entrepreneurial process. From the results you can determine certain specific factors that supplement Dyer’s pattern, especially it was determined that there are situational variables, deeply defined by family formative experiences and work experiences, that frame the whole model. In the same way, we could detect that formal education in Entrepreneurial Spirit, is more a complementary tool and a stimulant of previous situations than a fundamental variable of the entrepreneurial process.